Petroselinum sativum (Parsley) extract suppresses oxidative stress and inflammatory responses in human keratinocytes and reduces atopic dermatitis symptoms in mouse skin - Wang, Juan; Wu, Xiaoqian; Tang, Huihao; Liu, Zhiwei; Ding, Yun; Feng, Minyi; Wang, Shasha; Zuo, Jiaqi; Zhao, Qi; Li, Yaozhao; Zhai, Chuntao; Hu, Zhenlin; et al. (Frontiers in Pharmacology, 2025)
Petroselinum crispum (Mill.) Fuss (parsley), a traditional botanical drug used for treating skin conditions including atopic dermatitis (AD), has unclear effects on epidermal keratinocytes. This study investigated the antioxidant and anti-inflammatory properties of parsley extracts in human keratinocytes and evaluated their therapeutic potential in an experimental AD model. The aqueous, ethanolic, and hydro-ethanolic (HE) extracts of parsley were evaluated for total polyphenol and flavonoid metabolites (TPC, TFC) and antioxidant activity using DPPH and FRAP assays. In vitro, HaCaT cells were treated with tert-butyl hydroperoxide (t-BHP) and TNF-α/IFN-γ to induce oxidative stress and inflammation. Therapeutic efficacy was further evaluated in 2,4-dinitrofluorobenzene (DNFB)-induced AD-like mouse model. The results showed that HE extracts of parsley (HEP) contained the highest TPC and TFC and exhibited the strongest antioxidant activity, significantly improving cell viability and reducing ROS levels in t-BHP-treated cells. Mechanistically, HEP alleviated oxidative stress by activating Nrf2 pathway and enhancing the expression of antioxidant enzymes, such as superoxide dismutase (SOD) and catalase (CAT). In addition, HEP suppressed inflammatory cytokines IL-33, IL-6, and IL-8 expression by inhibiting JAK1/STAT1 and NF-κB signaling, and simultaneously increased the expression of skin barrier proteins, including filaggrin and claudin-1 in TNF-α/IFN-γ-stimulated HaCaT cells. Moreover, HEP application could alleviate AD-like symptoms in DNFB-induced mouse model, including reduced skin hyperplasia and decreased immune cells infiltration. These findings suggest that HEP modulates oxidative stress and inflammation through multiple signaling pathways, offering promising natural therapeutic agent for AD management.